2013
DOI: 10.1111/ijn.12029
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous vaginal delivery or caesarean section? What do Turkish women think?

Abstract: The aim of this study was to describe women's feelings, attitudes and beliefs about different modes of childbirth. A descriptive cross-sectional study was conducted at the obstetrics clinics of Ege University and Dr Ekrem Hayri Ustundag Obstetrics and Gynaecology Hospital in Izmir, Turkey. Three-hundred forty-two women who had given birth via spontaneous vaginal delivery (SVD) or caesarean section (C/S) between June and December 2009 voluntarily agreed to participate. Fifty-seven per cent of participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
1
8
1
1
Order By: Relevance
“…The type of delivery (vaginal or cesarean section), the interventions performed at delivery [25,26], and the communication skills of the midwife and physician who assist delivery are important obstetric factors affecting the way birth is perceived [14,23]. The type of the birth can cause traumatic effects, creating fear in especially in nulliparas and those who had negative previous birth experiences.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The type of delivery (vaginal or cesarean section), the interventions performed at delivery [25,26], and the communication skills of the midwife and physician who assist delivery are important obstetric factors affecting the way birth is perceived [14,23]. The type of the birth can cause traumatic effects, creating fear in especially in nulliparas and those who had negative previous birth experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Poor communication, which creates a traumatic effect at birth, also increases the preference of women for a cesarean section [4,25,41]. Sydsjö et al suggested that the rate of cesarean delivery increased by 5.2 times in the women who experienced traumatic pregnancies previously [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15% for 50% of countries on the average (1,2). Although caesarean section must be just performed based on medical indications, elective caesarean rate is rising.…”
mentioning
confidence: 99%